Implementation of vygotsky's developmental psychology theory to overcome mathematics learning anxiety - Subiantoro, Nezar; Lailiyah, Jeni Ifatul; Saputra, M. Amirudin Mangku; Nurwahid, Muhammad (LINEAR: Journal of Mathematics Education, 2025)
This study explores the application of Vygotsky's developmental psychology theory to overcome mathematics learning anxiety among students. It emphasizes the importance of key concepts such as Zone of Proximal Development (ZPD), Scaffolding, and the role of language as a mediating tool in the learning process. By fostering a collaborative learning environment, where students engage in group discussions and share ideas, this research highlights how emotional support can reduce the fear and anxiety often associated with mathematics. This research includes research studies using literature review methods. Data in the form of articles relevant to Vygotsky's theory and mathematical anxiety. Then the data is analyzed and concluded. Findings suggest that implementing social-emotional interventions, such as providing extra time for assignments and creating a safe learning atmosphere, can significantly increase students' self-confidence and reduce stress.